PENGARUH PERMAINAN SOCCER LIKE GAMES TERHADAP PEMAHAMAN BERMAIN SEPAK BOLA U12 BALI UNITED ACADEMY MATARAM - Ninda Lianda; Andi Anshari Bausad; Noor Akhmad (LPPM Institut Pendidikan Nusantara Global, 2023)
This Study is intended to analyze whether there is a positive and significant effect of playing soccer-like games on the understanding of playing soccer at U12 Bali United Academy Mataram. The method used in this study is an experimental method with a quantitative approach. One-group pretest-post-test design. The sample in this study was U12 Bali United Academy Mataram, consisting of 20 students. In taking research samples using saturated sample techniques. Furthermore, the data collection technique uses the game performance assessment instrument (GPAI). The results of the paired samples t-test obtained a significance value of 0.000 <0.05 for the results of understanding playing football. The conclusion from this study is that there is an influence of playing soccer-like games on increasing understanding of playing soccer. The recommendation from the author is to create and develop media soccer-like games that are more specific